Life history dynamics of evolving tumors: insights into task specialization, trade-offs, and tumor heterogeneity - Mahmoud Ahmed; Deok Ryong Kim (Cancer Cell International)
Abstract The evolution of cancer cells parallels species evolution in numerous ways. Variations arise and spread under the pressure of competition between cancer cells. Current investigations of tumor evolution echo earlier debates between biologists. These include the role of non-Darwinian mechanisms, the contribution of neutral evolution, and life history dynamics. The trade-off between proliferation and metastasis is the most well-studied application of life history theory to cancer evolution. This article briefly introduces some parallels between cancer and species evolution, focusing on the life history of evolving tumors. Next, we review evidence from simulation and experimental studies supporting task specialization and trade-offs in cancer. We also cover recent work on inferring tumor tasks from data. We then turn to the implications of multi-tasking and the utility of the theory in explaining critical aspects of tumor heterogeneity. Finally, we discuss some of the criticism and future directions of this research topic.